2016
DOI: 10.1039/c6ta00392c
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemically functional layer of hydrogenase extract on an electrode of large and tunable specific surface area

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 61 publications
0
14
1
Order By: Relevance
“…Hydrogen-converting enzymes are of particular interest for the use in hydrogen production as a clean energy carrier and energy generation in biofuel cells ( Armstrong et al, 2009 ; Chenevier et al, 2013 ). As shown for Escherichia coli ’s hydrogenases for example, these enzymes can be used for enhanced hydrogen production on surface-enlarged nanofiber electrodes ( Schlicht et al, 2016 ). Due to the steep thermal and chemical gradients prevailing in vent environments, enzymes of exceptional stability under various conditions (e.g., temperature or oxygen contents) can be expected to be found.…”
Section: Accessing the Uncultured Majority And Their Hydrogen-convertmentioning
confidence: 99%
“…Hydrogen-converting enzymes are of particular interest for the use in hydrogen production as a clean energy carrier and energy generation in biofuel cells ( Armstrong et al, 2009 ; Chenevier et al, 2013 ). As shown for Escherichia coli ’s hydrogenases for example, these enzymes can be used for enhanced hydrogen production on surface-enlarged nanofiber electrodes ( Schlicht et al, 2016 ). Due to the steep thermal and chemical gradients prevailing in vent environments, enzymes of exceptional stability under various conditions (e.g., temperature or oxygen contents) can be expected to be found.…”
Section: Accessing the Uncultured Majority And Their Hydrogen-convertmentioning
confidence: 99%
“…The frequency-dependent resistance arises from the capacitance C e (as 1/ωC): it reflects engagement of the cyclic contribution from reversible chemical steps ranging from binding/release of H 2 to atom/ion transfer, as well as electron transfers that are tightly coupled to these steps (30,31). Expressed another way, R e represents the DC resistance always offered by the combined electron relay and active site, whereas C e is analogous to a time-dependent charging and discharging of the active site (this is a Faradaic process because catalytic cycling allows electrons to flow).…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…All depositions have been carried out in a custom-built ALD reactor described elsewhere [ 33 ]. Titanium isopropoxide (( i PrO) 4 Ti) precursor was purchased from Sigma Aldrich and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…This result is in agreement with previous studies that showed that TiO 2 films deposited by ALD below 200 °C are amorphous, and that annealing at temperatures above 300 °C are typically required to obtain the crystallization of the films. Crystalline TiO 2 typically exhibits the anatase phase, but the rutile phase can also be achieved by ALD, using ozone or plasmas as coreactants [ 33 , 35 , 36 ]. The relative density of the ALD TiO 2 has been reported elsewhere to be 3.6 g/cm 3 [ 37 ].…”
Section: Methodsmentioning
confidence: 99%